Adventures in Licensing! How Librarians are Embracing and Affecting Change in Electronic Resources Licensing. Issue 1 (1st May 2017) - Duggan, Lori; Geuther, Christina; Halaychik, Corey; Hampton, Nancy
ABSTRACT: This article describes a program session about licensing electronic resources. The speakers discussed a range of licenses in the current electronic resources landscape and described current trends in the negotiation and management of licenses. They also explored the impact of workflow design on the accessibility of electronic resources at any institution.